Synthesis of Water-soluble Polyaniline by Using Different Types of Cellulose Derivatives. Issue 7 (September 2017) - Hussin, Hazira; Gan, Seng Neon; Mohamad, Sharifah; Phang, Sook Wai
Pure polyaniline (PAni) is insoluble in water. Water-soluble complexes of PAni with different of cellulose derivatives were successfully synthesized by using chemical oxidation polymerization of aniline in aqueous solution of cellulose derivatives. In this study, cellulose derivatives such as methylcellulose (MC), hydroxypropyl cellulose (HPC), and hydroxypropyl methylcellulose (HPMC) had been used as a steric stabilizer, aniline (Ani) as a monomer with hydrogen chloride (HCl) as an acidic dopant, and ammonium persulfate (APS) as an initiator. The chemical structure of PAni complexes were confirmed by using Fourier Transform Infrared Spectroscopy (FTIR). The interactions of PAni and cellulose derivatives were observable through Ultraviolet-Visible Spectroscopy (UV-Vis) in the wavelength range of 300 nm to 900 nm. The Standard Four-Point Probe Method was used for the conductivity measurements. In the electrical conductivity measurement, PAni in toluene was used as a control. The result showed that water-soluble PAni-cellulose derivatives gave higher conductivity value (9.47 × 10 −2 – 1.87 × 10 −1 S/cm) than the pristine PAni (1.60 × 10 −3 S/cm).